A study on characteristics of leader that members are preferred to ensure the successfulness of leader in managing their society/club in UiTM Melaka City Campus / Sheikh Mohd Eeqbal Mohd Khalid and Ruslin Rusli - Mohd Khalid, Sheikh Mohd Eeqbal; Rusli, Ruslin (2015)
There is many types of the leadership that being practices by the leader. This research focus on how the characteristics of leader can give impact towards his or her members of the society and club in UiTM Malacca City Campus. The involvement of student that guide and lead the flow of the associations. There have some characteristics that we want research towards the leader in UiTM Malacca City Campus. The characteristics is awareness, critical thinking, and teamwork. Every leader in the society and club is differ than other, they also have their own character. As a good leader, the leader should know how to mingle around with members of the society and club. By doing this research, we could find which character of the leader members of the society and club prefer to ensure successfulness of the society. Based on this research, we notice that majority of the members of the society club prefer leader who has a good awareness towards his or her members.